Inhibition of Human Cytomegalovirus Particle Maturation by Activation of Liver X Receptor - Liu, Bingnan; Ma, Yanping; Huang, Yujing; Liu, Zhongyang; Ruan, Qiang; Qi, Ying (Frontiers in Microbiology, 2022)
Human cytomegalovirus (HCMV), a herpesvirus family member, is a large, complex enveloped virus. The activation of liver X receptor (LXR) can significantly inhibit the replication of HCMV and weaken the virulence of progeny virus (unpublished data). Our results showed activated LXR affected some important viral protein expression and reduced cholesterol content in HCMV infected cells and virus particles. To further clarify the influence of activated LXR on HCMV replication, HCMV assembly and maturation processes were studied by transmission electron microscopy (TEM) in HCMV infected foreskin fibroblasts treated with LXR agonist GW3965. Results showed that activated LXR could reduce the envelope integrity of maturating virions. The functional stage of activated LXR on viral envelope integrity was mainly at virus assembly compartment (VAC) mediated envelopment but not structurally complete virus nucleocapsid formation and the egress of nucleocapsid from the nucleus to the cytoplasm mediated by nuclear egress complex. Reduced cholesterol synthesis and viral protein expression might interfere with the VAC-mediated envelopment. The nucleocapsid and tegument proteins enter the VAC area for the secondary envelope, which was interfered with and resulted in the defective particle, thereby affecting the amount and infectivity of the mature virus. The results indicate that inhibition of HCMV maturation is one mechanism of activated LXR inhibiting virus replication in infected cells.